Ruby falls - Phillips, Gin (Atlantic Crime, 2026)
"In 1928, a Chattanooga man disappears down a hole in the ground and discovers a 150-foot waterfall in the middle of a mountain that he names after his wife: Ruby Falls. Within months, visitors can buy tickets to see the falls for themselves. Ada Smith has been sneaking into the caves at night, entranced by the natural wonders around her and the freedom granted by this new underground world. But it's tough timing for a natural wonder. As the country flounders in the Great Depression, a shrewd public relations ploy seems like the only way to save Ruby Falls. A famous mind reader agrees to launch himself into the caverns where he will attempt to locate a hidden hatpin using only his psychic abilities. He'll be joined by five others: his manager, his wife, a guide, a Chattanooga businessman, and a reporter from the Chicago Times. But they're not alone in the caverns. Ada and another guide, Quinton, have been asked to follow the mind reader's party at a distance, staying out of sight. They are a safety net, in case of a broken leg or busted flashlights. One of them will be dead before the end of the day. Faced with a corpse and the stark reality that one of the people in her midst is a killer, Ada needs to get everyone--the murderer and the innocents--back aboveground before their light runs out"--